Olmesartan Decreased Levels of IL-1β and TNF-α, Down-Regulated MMP-2, MMP-9, COX-2, RANK/RANKL and Up-Regulated SOCs-1 in an Intestinal Mucositis Model - de Araújo Júnior, Raimundo Fernandes (PLoS One, 2014)
Methotrexate (MTX) is a pro-oxidant compound that depletes dihydrofolate pools and is widely used in the treatment of leukaemia and other malignancies. The efficacy of methotrexate is often limited by mucositis and intestinal injury, which are major causes of morbidity in children and adults. The aim of this study was to evaluate the effect of olmesartan (OLM), an angiotensin II receptor antagonist, on an Intestinal Mucositis Model (IMM) induced by MTX in Wistar rats. IMM was induced via intraperitoneal (i.p.) administration of MTX (7 mg/kg) for three consecutive days. The animals were pre-treated with oral OLM at 0.5, 1 or 5 mg/kg or with vehicle 30 min prior to exposure to MTX. Small intestinal homogenates were assayed for levels of the IL-1β, IL-10 and TNF-α cytokines, malondialdehyde and myeloperoxidase activity. Additionally, immunohistochemical analyses of MMP-2, MMP-9, COX-2, RANK/RANKL and SOCS-1 and confocal microscopy analysis of SOCS-1 expression were performed. Treatment with MTX + OLM (5 mg/kg) resulted in a reduction of mucosal inflammatory infiltration, ulcerations, vasodilatation and haemorrhagic areas (p<0.05) as well as reduced concentrations of MPO (p<0.001) and the pro-inflammatory cytokines IL-1β (p<0.001) and TNF-a (p<0.01), and increase anti-inflammatory cytocine IL-10 (p<0.05). Additionally, the combined treatment reduced expression of MMP-2, MMP-9, COX-2, RANK and RANKL(p<0.05) and increased cytoplasmic expression of SOCS-1 (p<0.05). Our findings confirm the involvement of OLM in reducing the inflammatory response through increased immunosuppressive signalling in an IMM. We also suggest that the beneficial effect of olmesartan treatment is specifically exerted during the damage through blocking inflammatory cytocines.